ANÁLISIS GENÓMICO DE PARVOVIRUS CANINO POR PCR - RFLP A PARTIR DE AISLAMIENTOS DE CASOS CLÍNICOS SINTOMÁTICOS TOMADOS EN BOGOTÁ, COLOMBIA. ESTUDIO PRELIMINAR - Castillo, Ángela; Grupo de enfermedades infecciosas, Microbiología Agrícola y Veterinaria, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
With the objective of detemúning the genotypes of canine parvovirus (CPV) circulating in Bogotá, 56 fecal and blood samples were obtained from younger dogs, up to a year old with hemorrhagic gastroenteritis for its analysis by the polymerase chain reaction - fingerprints (PCR - RFLP) assay. DNA fragments were obtained from (2,2 Kb) a representative vaccine strain of parvovirus type -2 (CPV-2) and from the four fecal samples were amplified by the PCR assay; they were not obtained from the amplification of the blood samples. The amplified products were digested by the restriction enzyme Rsa I, pemútting the identification of genotypes PCV-2a and PCV-2b and the differentiation of CPV-2 from CPV-2a and CPV-2b.